Application Fields, Positions, and Bioinformatic Mining of Non-active Sites: A Mini-Review - Wang, Xiaoxiao; Ma, Qinyuan; Shen, Jian; Wang, Bin; Gao, Xiuzhen; Zhao, Liming (Frontiers in Chemistry, 2021)
Active sites of enzymes play a vital role in catalysis. Research has been focused on the interactions between active sites and substrates to understand the biocatalytic process. However, some non-active sites distal to the catalytic cavity also participate in catalysis by maintaining the catalytic conformations. Therefore, some researchers have begun to investigate the roles of non-active sites in proteins, especially for enzyme families with different functions. In this mini-review, we focused on recent progress in research on non-active sites of enzymes. First, we outlined the two major research fields with non-active sites as direct targets, including understanding of enzymatic mechanisms and enzyme engineering. Second, we classified the positions of reported non-active sites in enzyme structures and studied the molecular mechanisms underlying their functions, according to the literature related to non-active sites. Finally, we summarized the bioinformatics analysis on mining non-active sites as targets for protein engineering.